<IN> IIS QUI AD ME TAMQUAM CHRISTIANI DEFEREBANTUR, HUNC SUM SECUTUS MODUM. ŚRODKI DOWODOWE ZASTOSOWANE W PROCESIE CHRZEŚCIJAN PONTYJSKICH W RELACJI PLINIUSZA MŁODSZEGO (EP. 10,96) - Jońca, Maciej (Zeszyty Prawnicze, 2017)
<In>iis quiad me tamquam christiani deferebantur, hunc sum secutus modum. Evidence Applied in the Persecution of Pontian Christians According to Pliny the Younger (Ep. 10,96) Summary In 1st and 2nd centuries A. D. Christians were occasionally persecuted and punished just for being Christians (nomen christianurn). The letter drafted by Pliny the Younger to emperor Trajan constitutes the most significant non-Christian source providing information on the procedures applied in these circumstances. Pliny mentions three groups of people that emerged due to the presented above activities: the Christians, who did not renounce their faith at court, falsely accused pagans and apostates. A governor asked those who refused to abandon their faith before executing them. The execution did not apply to Roman citizens who, according to law, were sent to Rome. Apostates and pagans underwent special tests. In order to prove that they were not Christians the governor made them call the names of gods and perform sacrifices before the image of the emperor and gods, which was followed by the course on Christ. However, it was not a refusal to participate in the rituals that led to a punishment but their attachment to Christian community. Therefore, a ceremony of purely religious nature became a real proof applied in judicial proceedings. Although the emperor expressed his approval for governor’s measures, he did not establish any general rule concerning the prosecution and punishments of Christians.